The Role of Family in the Social and Emotional Development of Adolescents from Broken Homes: A Case Study in Seulalah Baru Village - Salsabila, Natasya; Chalidaziah, Wan; Ilyas, Sabrida M. (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2023)
This study aims to explore in depth the role of the family in the social and emotional development of adolescents from broken homes in Seulalah Baru Village, Langsa City. The increasing prevalence of family disharmony and parental divorce has generated significant psychosocial impacts on adolescent well-being. This research employed a qualitative approach with a case study design, allowing the researcher to examine adolescents’ subjective experiences and family interaction dynamics within their sociocultural context. The participants consisted of three broken-home families selected through a purposive sampling technique. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that adolescents’ social and emotional development in broken-home families is influenced by parenting patterns, communication quality, emotional support, religious values, and social environment. The study identifies family religiosity and community support as protective factors that mitigate emotional instability and maladaptive behavior among adolescents. The results further emphasize that the quality of emotional relationships and family communication is more crucial to adolescents’ socio-emotional well-being than the structural completeness of the family itself. Theoretically, this study strengthens Bandura’s social learning theory and Bronfenbrenner’s ecological theory. Practically, it provides a foundation for developing family support programs rooted in cultural and spiritual values, contributing to more holistic and contextually relevant interventions for adolescents from broken-home families.